Normative Study of Violations of Consumer Rights in The Practice of Fuel Packaging: Perspective of Law No. 8 Year 1999 - Wahyuni, Husnia Hilmi; Afda'u, Faisal; Ahmad, Ridho Sadillah (UNISKA LAW REVIEW, 2024)
This research aims to normatively examine the violations of consumer rights in the practice of fuel adulteration carried out by unscrupulous individuals within PT Pertamina Patra Niaga. This practice not only harms consumers economically and in terms of safety but also violates the statutory provisions that guarantee consumer protection. The method used is normative legal research with a statutory approach and literature review. The findings indicate that the practice of fuel adulteration constitutes a violation of Law Number 8 of 1999 concerning Consumer Protection, particularly the right to comfort, safety, and security in consuming goods and/or services. Furthermore, this action can also be classified as a criminal offense due to endangering public interests. Therefore, strict law enforcement and closer supervision of fuel distribution and processing are necessary to ensure the protection of consumer rights.